Development, Implementation, and Use of a Neurology Therapeutics Committee. (14th February 2019) - Clark, Edward B.; Butterfield, Russell J.; Filloux, Francis M.; Bonkowsky, Joshua L.
Innovative therapeutics are transforming care of children with previously untreatable neurological disorders. However, there are challenges in the use of new therapies: the medicine may not be effective in all patients, administration may not be tolerated, and matching therapy choice to patient is complex. Finally, costs are high, which imposes financial burdens on insurance companies, families, and the health-care system. Our objective was to address challenges for clinical implementation of the new therapeutics. We sought to develop a process that would be personalized for patient and disease, encourage appropriate use of a therapeutic agent while mitigating pressure on a clinician to prescribe the therapy in all instances, and assist third-party payers in approving therapeutic use based on safety and efficacy. We report our creation of a Neurology Therapeutics Committee for pediatric patients. We review the committee's mechanisms, describe its use and report outcomes, and suggest the Neurology Therapeutics Committee's broader applicability.